KAJIAN MINAT BELANJA KEBUTUHAN POKOK WARGA PERUMAHAN ROYAL MATARAM - Anna Apriana Hidayanti; Agus Khazin Fauzi (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2017)
The development of more and more modern shopping places and compete in Mataram City this is not separated from the pattern of consumption of the people of Mataram city that has changed, the lifestyle changes of people who used to just shop in traditional markets, is now beginning to switch to shopping in the modern market. The increasing number of modern markets that offer products with various brands and various promotional prices as well as the convenience of shopping is a selling point offered by modern markets not just clothing needs that sell with various products and brands, but the food needs are also very complete with various brands in the country And abroad so that consumers will have more choices in meeting their basic needs, food needs and clothing needs The increasing pattern of public consumption is accompanied by the increasing income of the people of Mataram City itself as well as the royal Mataram resident , the Royals purchasing power of a higher product, the change of interest in a basic needs of society is also very felt, formerly shopping modern market only for Look around or buy the needs of luxury accessories, but now shopping in the modern market is a Role shopping which means the form of shopping activities to get the best product for yourself and for others where shopping activities in the modern market is a necessity or a daily task that is not Can be left to meet the needs of food and clothing needs, so researchers interested to know what variables affect the selection of shopping with binary logistic regression method, where the variables studied as a dependent variable is the place of shopping / market: Ar modern (1) or non modern market / traditional market (0). Lifestyle changes such as those felt or experienced also by Royal Mataram resident this matter is influenced by several factors and in this research the factors that affect the people who shop for basic needs (foods and clothings) are income variables, many family members and last education because the value of sig . Greater than the value of α = 5% Keywords: Role shopping, Logistic Regression, categorical scale